Diseño de estrategias para el liderazgo efectivo en la gestión administrativa de la Unidad Educativa del Milenio" Jatun Kuraka Otavalo". - Navarro, Zoila A. (2022)
This research analyzes the effective leadership in the administrative management ofthe Millennium Educational Unit "Jatun Kuraka Otavalo"; for which, and in accordance withthe specific objectives, the theoretical framework was structured on the variables of effectiveleadership and administrative management. All of these based on bibliographic research withupdated physical and digital information. Such as, internet articles, and free circulationeducational magazines. For the fulfillment of the second objective, and due to itscharacteristics, it is a descriptive and explanatory investigation with a mixed approach; as itis a process that collects, analyzes, and discharges quantitative and qualitative data in thesame study. The research tool that was designed and applied consists of a questionnaire asthe main instrument. Among the main findings of this study was to determine that theeducational actors involved do not agree with the existing leadership, for the lack ofcommunication, which has notably worsened interpersonal relationships, and therefore thequality of administrative management results deficient. However, there is the predispositionof educational actors, for participation in the generation of a proposed solution to theproblem investigated. Finally, and in accordance with the third objective, the proposalconsists of design strategies to strengthen effective leadership in administrativemanagement, based on the current Institutional Educational Project (PEI).